Study of seed germination and dormancy of Prosopis farcta, Launaea acanthodes and Cressa cretica in pistachio orchards of Rafsanjan - M. Khajeh-Hosseini; M. Alinaghizadeh; S.A. Hosseini; M.H. Rashed Mohasel (علوم و فناوری بذر ایران)
In order to study the seed germination and dormancy of 3 weed species (Prosopis farcta, Launaea acanthodes and Cressa cretica) of pistachio orchards in Rafsanjan, Iran, three factorial experiments were conducted based on completely randomized design with four replications, at the faculty of agriculture, Vali-E-Asr university of Rafsanjan, Iran, in 2014. Weed seeds were collected from five different regions of Rafsanjan, including Markazi, Anar, Koshkoiyeh and Nogh. Dormancy breaking treatments for P. farcta included scarification by scalpel and sandpaper, chemical scarification by sulfuric acid (30 and 40 min), and distilled water as control. Treatments for L. acanthodes included gibbereilic acid (250, 500 and 1000 ppm), KNO3 (500 and 1000 ppm), cold stratification (for 1, 3 and 5 weeks). Treatments for C. cretica included scarification by scalpel and sandpaper, sulfuric acid (5 and 10 minute), boiling water (for 15 and 30 min) and distilled water as control. Results showed that seed germination percentage (SGP) and mean germination time (MGT) was significantly different among different weed populations and dormancy breaking methods. Seed scarification by scalpel and sulfuric acid resulted in highest SGP in P. farcta and C. cretica. For all L. acanthodes populations, cold stratification for 5 weeks increased SGP, especially in Anar (94 %). Using KNO3 at 500 ppm, and 250 ppm gibbereilic acid, significantly increased germination percentage of L. acanthodes seeds (79 and 74.8 %, respectively), but higher concentration of KNO3 and gibbereilic acid, reduced germination percentage.